Complex Cells in the Cat Striate Cortex Have Multiple Disparity Detectors in the Three-Dimensional Binocular Receptive Fields - Sasaki, Kota S. (J Neurosci, 2010)
Along the visual pathway, neurons generally become more specialized for signaling a limited subset of stimulus attributes and become more invariant to changes in the stimulus position within the receptive fields (RFs). One of the likely mechanisms underlying such invariance appears to be pooling of detectors located at different positions. Does such spatial pooling occur for disparity-selective neurons in primary visual cortex? To examine whether the three-dimensional (3D) binocular RFs are constructed by pooling detectors for binocular disparity, we investigated binocular interactions in the 3D space for neurons in the cat striate cortex. Approximately one-third of complex cells showed the spatial pooling of disparity detectors to a significant degree, whereas the majority of simple cells did not. The degree of spatial pooling of disparity detectors along the preferred orientation axis was generally larger than that along the axis orthogonal to the orientation axis. We then reconstructed 3D binocular RFs in their complete form and examined their structures. Disparity tuning curves were compared across positions along the orientation axis in the RFs. A small population of cells appeared to show a gradual shift of the preferred disparity along this axis, indicating that they can potentially signal inclination in the 3D space. However, the majority of cells exhibited a position-invariant disparity tuning. Finally, disparity tuning curves were examined for all oblique angles in addition to horizontal and vertical. Tunings were broadest along the orientation axis as the disparity energy model predicts.